Prior contact lens wear reduces susceptibility of the superficially-injured cornea to bacterial adhesion - Yujia Yang; Orneika Flandrin; Sara J. Abboud; Eric Jedel; David J. Evans; Suzanne M. J. Fleiszig (PLoS ONE, 2026)
Contact lens wear in humans and mice is consistently associated with asymptomatic corneal parainflammation. Here, we tested the hypothesis that the corneal response to lens wear alone can function to protect it against bacterial adhesion enabled by superficial injury. One eye only of mT/mG-LysMcre mice (cell membranes red; Lyz2 + cells green) wore a contact lens for 4–6 days. After lens removal, mice were anesthetized and both corneas superficially-injured before bacterial inoculation with either a mouse eyelid commensal ( Macrococcus epidermidis ) or a corneal pathogen ( Pseudomonas aeruginosa ). Inoculation was repeated hourly for 4 hours under anesthesia before euthanasia. Enucleated eyes were fixed overnight, and adherent bacteria visualized using a universal 16S rRNA-targeted FISH probe ( M. epidermidis ) or Blue Fluorescent Protein ( P. aeruginosa ). Confocal imaging and Imaris software were used to quantify bacterial adhesion and location in the epithelium, and also the number, location and morphology of Lyz2 + cells. For both commensal and P. aeruginosa , prior lens wear resulted in reduced adhesion to the superficially-injured corneas (~46% and ~57% respectively). In both instances this correlated with increased numbers of corneal Lyz2 + cells. Other details differed for the two bacterial types. For the commensal, prior lens wear resulted in bacteria penetrating deeper into the epithelium versus contralateral eyes, with Lyz2 + cells extending their processes further into the epithelium and localizing closer to the cornea surface. For P. aeruginosa , prior lens wear resulted in adherent bacteria closer to the cornea surface, and Lyz2 + cells moving further away from it. Moreover, while overall Lyz2 + cell sphericity increased for P. aeruginosa with prior lens wear versus contralateral eyes, it showed no overall change for the commensal. Lyz2 + cell volume in the central cornea was decreased for P. aeruginosa with prior lens wear but increased for the commensal. Thus, corneal responses to prior lens wear can quantitively reduce bacterial adhesion to superficially-injured corneas correlating with a Lyz2 + cell response for both a commensal and a pathogen, with differences in details for the two bacterial types. How continued lens wear supersedes this protective response to promote P. aeruginosa infection pathogenesis remains to be determined, as does the relationship to the Lyz2 + cell response.